A spatial predictive model for malaria resurgence in central Greece integrating entomological, environmental and social data. - Panagiotis Pergantas; Andreas Tsatsaris; Chrisovalantis Malesios; Georgia Kriparakou; Nikolaos Demiris; Yiannis Tselentis (PLoS ONE)
Malaria constitutes an important cause of human mortality. After 2009 Greece experienced a resurgence of malaria. Here, we develop a model-based framework that integrates entomological, geographical, social and environmental evidence in order to guide the mosquito control efforts and apply this framework to data from an entomological survey study conducted in Central Greece. Our results indicate that malaria transmission risk in Greece is potentially substantial. In addition, specific districts such as seaside, lakeside and rice field regions appear to represent potential malaria hotspots in Central Greece. We found that appropriate maps depicting the basic reproduction number, R0, are useful tools for informing policy makers on the risk of malaria resurgence and can serve as a guide to inform recommendations regarding control measures.